1997
DOI: 10.1029/97wr02408
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of microporosity by nuclear magnetic resonance relaxation of water imbibed in porous media

Abstract: Abstract. On the basis of the nuclear magnetic resonance (NMR) relaxation of imbibed water, we evaluated the interparticle and intraparticle pore sizes in packed beds of silica materials of known particle sizes and microporous structure. The NMR relaxation distribution is scaled by the surface relaxivity parameter p, which incorporates a surface area to volume ratio (So/Vo) term, to yield a corresponding pore size distribution. The NMR-derived pore sizes of nonporous silica sand agreed with the expected interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 19 publications
2
63
0
Order By: Relevance
“…Desiccation may cause irreversible changes in pore structure, which in turn will affect the actual POSD of the soils. The Image analysis or Microscopy requires approach a large quantity of two-dimensional information for the desired three-dimensional pore structure information and it is time-consuming (Gallegos and Smith 1988;Hinedi et al 1997;Giesche 2006;Kate and Gokhale 2006;Minagawa, et al 2008;Benjamini et al 2014;Wang et al 2016). None of those methods are suitable for this present study because the tested soil is a special kind of low density (dry density, ρ d =1.30 g/cm 3 ) granite residual soil with grain size distribution ranging from gravel to clay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desiccation may cause irreversible changes in pore structure, which in turn will affect the actual POSD of the soils. The Image analysis or Microscopy requires approach a large quantity of two-dimensional information for the desired three-dimensional pore structure information and it is time-consuming (Gallegos and Smith 1988;Hinedi et al 1997;Giesche 2006;Kate and Gokhale 2006;Minagawa, et al 2008;Benjamini et al 2014;Wang et al 2016). None of those methods are suitable for this present study because the tested soil is a special kind of low density (dry density, ρ d =1.30 g/cm 3 ) granite residual soil with grain size distribution ranging from gravel to clay.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies reported the potentiality of NMR relaxometry to assess the POSD of porous media in a fast and non-destructive way (Kleinberg 1994;Strange et al 1993; Hinedi al. 1997;Milia et al 1998;Dunn et al 2002;Ramia et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This time constant is generally measured in controlled laboratory experiments (e.g. Hinedi et al 1997) and in borehole logging by switching the static applied magnetic field for various lengths of time. Tlis procedure is not possible for the surfkce geophysicalmeasurementswhere the earth's magnetic field is used.…”
Section: Relaxationmentioning
confidence: 99%
“…This time constant is generally measured in controlled laboratory experiments (e.g. Hinedi et al 1997) and in borehole logging by switching the static applied magnetic field for various lengths of time. This procedure is not possible for the surface geophysical measurements where the earth's magnetic field is used.…”
Section: Relaxation Timesmentioning
confidence: 99%